2017
DOI: 10.18488/journal.62.2017.44.82.94
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Accountants Unethical Behavior and Corporate Failures

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…By practising REM activities, managers realize that they must sacrifice future cash flows to fulfil short-lived benchmarks. However, because REM involves managerial decisions related to operational strategies and investments, REM becomes more difficult to detect and avoid its impacts on cash flows (Kothari, Mizik, & Roychowdhury, 2012;Chidoko and Mashavira, 2014;Salvioni and Gennari, 2014;Razek, 2014;Eshiet, 2017;Mejdoub and Arab, 2017;Oitsile., Galebotswe and Sekwati, 2018;Chang'ach, 2018). Previous research indicates that non-fraudulent AEM is less harmful to current stockholders than REM because it does not weaken a company's cash flows (Roychowdhury, 2006;Cohen & Zarowin, 2010;Kothari et al, 2012;Ali, et.al.…”
Section: Real Earnings Managementmentioning
confidence: 99%
“…By practising REM activities, managers realize that they must sacrifice future cash flows to fulfil short-lived benchmarks. However, because REM involves managerial decisions related to operational strategies and investments, REM becomes more difficult to detect and avoid its impacts on cash flows (Kothari, Mizik, & Roychowdhury, 2012;Chidoko and Mashavira, 2014;Salvioni and Gennari, 2014;Razek, 2014;Eshiet, 2017;Mejdoub and Arab, 2017;Oitsile., Galebotswe and Sekwati, 2018;Chang'ach, 2018). Previous research indicates that non-fraudulent AEM is less harmful to current stockholders than REM because it does not weaken a company's cash flows (Roychowdhury, 2006;Cohen & Zarowin, 2010;Kothari et al, 2012;Ali, et.al.…”
Section: Real Earnings Managementmentioning
confidence: 99%
“…Otros autores basan las definiciones en el actuar de las personas, un ejemplo claro es planteado por Miranda (1970) quien afirma que los fraudes financieros son delitos de gente inteligente avezada en los negocios, conocedora de las leyes y reglamentos y de las artimañas para eludir sanciones, influyente por su poder corruptor, y que tiene relaciones mundanas, políticas y con los funcionarios (p. 117). Por su parte, Enobong (2017) se enfoca en afirmar que los comportamientos antiéticos de los profesionales dejan consecuencias negativas principalmente en las organizaciones desencadenando perdidas monetarias y escándalos de índole financiero.…”
Section: Fundamentos Teóricos Del Fraude Financierounclassified
“…At the end of the 20 th century, high-profile corporate accounting scandals which led to the collapse of well-established companies across the globe have also been witnessed in Nigeria [9]. The business environment in this country is also plagued with ethical problems associated with corporate scandals involving large companies [10]. In Nigeria alone, it was reported that there were 1,639 cases with losses of 18.5 million USD in 2012, 314.5 million USD with 3,380 cases in 2013, and 3,756 cases with losses of 254.5 million USD in 2014 [11].…”
Section: Introductionmentioning
confidence: 99%